2015
DOI: 10.1111/apt.13334
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Randomised clinical trial: the clinical efficacy and safety of an alginate‐antacid (Gaviscon Double Action) versus placebo, for decreasing upper gastrointestinal symptoms in symptomatic gastroesophageal reflux disease (GERD) in China

Abstract: SummaryBackgroundThere is a paucity of large‐scale studies evaluating the clinical benefit of the Gaviscon Double Action (DA) alginate‐antacid formulation for treating gastroesophageal reflux disease (GERD) symptoms.AimRandomised double‐blind placebo‐controlled parallel‐group study to evaluate efficacy and safety of Gaviscon DA in reducing heartburn, regurgitation and dyspepsia symptoms in individuals with mild‐to‐moderate GERD in China.MethodsParticipants with symptomatic GERD (n = 1107) were randomised to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
16
0
4
Order By: Relevance
“…This was a randomized, double‐blind, placebo‐controlled study that used a validated patient‐reported outcome instrument, the reflux disease questionnaire, as the primary end‐point. Chinese GERD patients receiving DA alginate antacid tablets reported statistically significantly greater improvement in GERD symptoms (heartburn, regurgitation and dyspepsia) after 7 days of treatment . Taken together, findings from the pH monitoring and symptom relief studies support the efficacy of DA alginate antacid tablets for treating post‐prandial acid reflux and heartburn, and for short‐term symptom relief in GERD.…”
Section: Discussionmentioning
confidence: 99%
“…This was a randomized, double‐blind, placebo‐controlled study that used a validated patient‐reported outcome instrument, the reflux disease questionnaire, as the primary end‐point. Chinese GERD patients receiving DA alginate antacid tablets reported statistically significantly greater improvement in GERD symptoms (heartburn, regurgitation and dyspepsia) after 7 days of treatment . Taken together, findings from the pH monitoring and symptom relief studies support the efficacy of DA alginate antacid tablets for treating post‐prandial acid reflux and heartburn, and for short‐term symptom relief in GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Placebo pills contained medically non-effective mannitol [15,16] (Mannitol 99.5 T, highly-dispersed silicon dioxide 0.5 T) and matched the topiramate pills in appearance. Blood samples were drawn 60 min after administration to determine the topiramate plasma concentration at its peak, shortly before the start of the MR measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article. 2…”
Section: Acknowledgementmentioning
confidence: 99%